2019
DOI: 10.1155/2019/6416941
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Novel Polysaccharide-Iron(III) Complex in Auricularia auricula Potentially Used as an Iron Supplement

Abstract: Iron deficiency anemia has been a widespread disease. As an effective and stable iron supplement, the physiochemical properties of the polysaccharide iron complex have been widely studied. In this study, we characterized a novel polysaccharide-iron(III) complex extracted in an edible fungal species Auricularia auricular (AAPS-iron(III)). The highest iron content (28.40%) in the AAPS-iron(III) complex was obtained under the optimized preparation conditions including an AAPS to FeCl3∙6H2O ratio of 2:3 (w/w), a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 57 publications
(65 reference statements)
3
41
0
Order By: Relevance
“…The outcomes obtained in this study were generally consistent with those of previous reports, 8 , 33 which showed that the DPPH and ABTS scavenging activities of polysaccharides were higher than those of polysaccharide–iron(III) complexes. The difference in the antioxidant activities can be explained by the presence of numerous active hydroxyl and carboxyl groups in the structure of AP, particularly in galacturonic acid, which can act as electron donors to the free radicals.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The outcomes obtained in this study were generally consistent with those of previous reports, 8 , 33 which showed that the DPPH and ABTS scavenging activities of polysaccharides were higher than those of polysaccharide–iron(III) complexes. The difference in the antioxidant activities can be explained by the presence of numerous active hydroxyl and carboxyl groups in the structure of AP, particularly in galacturonic acid, which can act as electron donors to the free radicals.…”
Section: Resultssupporting
confidence: 92%
“… 31 The spectrum of the AP–Fe(III) complex exhibited four new peaks at 849, 688, 640, and 466 cm –1 , which were primarily attributed to the structure of the β-FeOOH group in the fabricated complex. 9 , 32 , 33 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 However, the long-term use of oral iron supplements has been shown to cause many gastrointestinal disorders including, nausea, vomiting, abdominal pain, and constipation. [18][19][20] Therefore, it would be better to develop functional foods to circumvent the prevalence of anemia and improve the iron bioavailability. Among functional foods, prebiotic containing-products are believed to be efficient in improving the iron uptake due to the formation of the prebiotic-iron complex, which can effectively enhance the iron bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…The DSC curves of succinoglycan and SCx are shown in Figure 6 b, and the heat flow values corresponding to the endothermic peak temperature are listed in Table 2 . The endothermic peak of DSC is typically due to the breakdown of hydrogen bonds and loss of hydroxyl groups when the sample is heated [ 55 ]. In the process of heating, the loss of water attached to the hydroxyl or carboxyl groups of succinoglycan leads to the breakdown of hydrogen bonds inside the hydrogels, which induces the phase transition of SCx.…”
Section: Resultsmentioning
confidence: 99%